Câmara e agenda 21 regional para uma rede de cidades sustentáveis: a região metropolitana da baixada santista - Carmo, Silvia de Castro Bacellar do (Universidade Federal de São Carlos, 2004)
The majority of the metropolitan regions, urban agglomerates and Brazilian cities live together with a degraded urban environment, resulting from a non-planned spatial expansion, lack of basic infrastructure, inefficiency of health and cultural systems, social exclusion, and from a non-planned prioritization of economic activities. One may also observe an increase in the metropolization process, where cities are united by their economic vocation or by conurbation processes, acquiring a new characterization, represented by political-institutional aspects. Concurrently, there has been an increase in global awareness as to the anthropic activity consequences over ecosystems and the repercussion of the current degradation on communities life conditions. The sustainable development parameter arises as a path to be followed in order to prevent exhausting natural resources and for the conquering of a worthy quality of life for all humankind, being the Agenda 21 one of the main instruments to be used within a strategic and participative process. The search for sustainability for the cities of a metropolitan region orients the development of this study. Establishing as spatial field of research the Baixada Santista Metropolitan Region, and adopting a profile of the institutional and socio-environmental dimension, one may promote a systematization of the planning and management structure of its nine municipalities, and of the whole set, as support to confirm the hypothesis that the search for metropolitan sustainability depends on the implementation of a metropolitan committee and of a metropolitan Agenda 21. This systematization was elaborated from a theoretical and reflexive investigation into the concepts and guiding vectors of a sustainable city: the urban environmental planning tendencies and the Brazilian legal and institutional aspects of the environmental question; through selection of foreign and national experiences of Local Agendas 21; through investigation of the region s Local Agendas 21; and, finally, through interviews and questionnaires applied to the municipalities, public agencies and appointed metropolitan agents. The result demonstrated a political-institutional integration geared towards economic dimension, a tendency to isolated and momentary solutions and the absence of effective participative processes; but, on the other hand, it has pointed to a viability of alterations in the current socio-institutional conjuncture, with the real activation of the Metropolitan Agenda 21 and with normative alterations in the official jurisdiction of the shared metropolitan representation.
Keywords: Planejamento urbano; Agenda 21; Região Metropolitana; Sustentabilidade ambiental urbana; ENGENHARIAS